2013
DOI: 10.4314/sajas.v43i2.4
|View full text |Cite
|
Sign up to set email alerts
|

Crossbreeding to increase beef production: additive and non-additive effects on weight traits

Abstract: ________________________________________________________________________________ AbstractUsing breed differences effectively facilitates high productivity and profitability. Thus, the objective of the study was to estimate direct and maternal additive and heterosis effects for growth traits (birth weight, weaning weight, 19-month weight of heifers and cow weight) from five purebred and 24 crossbred breed types. Afrikaner (A), Brahman (B), Charolais (C), Hereford (H) and Simmentaler (S) were evaluated as purebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 20 publications
(23 reference statements)
0
13
2
1
Order By: Relevance
“…The latter effect is substantially greater than the same effect estimated in the present study. Estimates of average individual heterosis effects on birth weight and 205-day weight from Theunissen et al (2013) were 1.2 and 14.7 kg, respectively, and again the effect on 205-day weight was greater than was observed here. There are multiple plausible explanations for the convergence of direct effects on birth and 205-day weights in the present study.…”
Section: Resultscontrasting
confidence: 42%
See 2 more Smart Citations
“…The latter effect is substantially greater than the same effect estimated in the present study. Estimates of average individual heterosis effects on birth weight and 205-day weight from Theunissen et al (2013) were 1.2 and 14.7 kg, respectively, and again the effect on 205-day weight was greater than was observed here. There are multiple plausible explanations for the convergence of direct effects on birth and 205-day weights in the present study.…”
Section: Resultscontrasting
confidence: 42%
“…The maternal effect of the NG on birth weight and preweaning growth was less than that of the BN and, together with the negative effect on cow weight, indicated the potential for reduced feed intake on the part of the NG cows. In an earlier crossbreeding experiment, which was also conducted at Vaalharts Research Station, Theunissen et al (2013) found the differences between AF and SM direct effects on birth weight and 205-day weight were 1.8 ± 2.8 and 27.3 ± 12.9 kg, respectively. The latter effect is substantially greater than the same effect estimated in the present study.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Carcass data were collected at the Animal and Dairy Research Institute, Irene, South Africa. Thus, parameters for the simulation experiments described hereafter were drawn from previously published literature [18] [24] [25] [26].…”
Section: Methodsmentioning
confidence: 99%
“…Breed-specific genetic effects, following [30], on the phenotypes used in the simulations for this study were taken from the previously published work of [24] [25] [26]. Specifically, phenotypes were simulated for four breed groups as follows:…”
Section: Methodsmentioning
confidence: 99%